Multitasking on a Single Device: Arousal and the Frequency, Anticipation, and Prediction of Switching Between Media Content on a Computer. (7th January 2014) - Yeykelis, Leo; Cummings, James J.; Reeves, Byron
<x xml:space="preserve">Abstract</x> This study measured arousal responses to multitasking by recording switches between content on personal computers over a day. Results showed that switches occurred every 19 seconds, more often than has been reported in previous research. Arousal was highest at the point of a switch with declines in skin conductance afterward. Switches were also preceded by a 12‐second period of increasing skin conductance. 2 new methods were used, one an original application that recorded screen shots, and another that measured changes in skin conductance during the day using a wrist sensor. Results are discussed in light of increasing use of single devices displaying multiple types of content, rather than multitasking that occurs when attention is divided between content on multiple devices.